Effectiveness of Three-Dimensional Animated Cartoon Stories Strategy on Helping Primary School Female First-graders Acquire Skills of Writing Arabic Alphabet in Different Positions - Khan, Nilan Adnan (Journal of Educational and Psychological Sciences, 2022)
The current study aims to examine the effectiveness of three-dimensional animated cartoon stories strategy on helping primary school female first-graders acquire skills of writing Arabic alphabet in different positions. To achieve the objectives of the study, the researcher constructed tools that consisted of (28) scenarios for all the letters, created (6) 3D animated cartoon videos including (6) letters taken from Unit Two of "Laughty" Course for Primary One, First Semester. Also, the researcher constructed achievement test (pre and post). To find out the effectiveness of this strategy, the researcher used the descriptive approach and the quasi-experimental approach on a sample of (88) female first graders at 35th School in Mecca during the first semester of the academic year thirty-fifth school in Makkah during the first semester of the academic year 1438 - 1439H. The sample was divided into two groups: experimental group (44) and control group (44). The results revealed that there are statistically significant differences at (α≤ 0.05) between the mean scores of the posttests of the experimental group and the posttests of the control group in favor of the experimental group. Furthermore, the researcher recommended.
Keywords: Curricula and teaching methods; Cartoon films; Primary school; writing skills; Teaching aids